2022
DOI: 10.1186/s13613-022-01006-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of non-invasive ventilation compared with extracorporeal carbon dioxide removal for acute hypercapnic exacerbations of chronic obstructive pulmonary disease

Abstract: Background Patients presenting with acute hypercapnic respiratory failure due to exacerbations of chronic obstructive pulmonary disease (AECOPD) are typically managed with non-invasive ventilation (NIV). The impact of low-flow extracorporeal carbon dioxide removal (ECCO2R) on outcome in these patients has not been explored in randomised trials. Methods Open-label randomised trial comparing NIV (NIV arm) with ECCO2R (ECCO2R arm) in patients with AEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…However, there are substantial differences in the CO 2 removal capacities of the ECCO 2 R devices used in recent studies, and the optimal blood flow required for clinical practice is yet to be defined (14–17). Although randomized controlled trials (RCTs) are now being published (8, 18, 19), the efficacy of ECCO 2 R devices in acute or acute on chronic hypercapnic respiratory failure is poorly understood. In part, this is because of the heterogeneity of the patient pathologies including those with acute and chronic hypercapnic acidosis (11, 14, 16, 20).…”
mentioning
confidence: 99%
“…However, there are substantial differences in the CO 2 removal capacities of the ECCO 2 R devices used in recent studies, and the optimal blood flow required for clinical practice is yet to be defined (14–17). Although randomized controlled trials (RCTs) are now being published (8, 18, 19), the efficacy of ECCO 2 R devices in acute or acute on chronic hypercapnic respiratory failure is poorly understood. In part, this is because of the heterogeneity of the patient pathologies including those with acute and chronic hypercapnic acidosis (11, 14, 16, 20).…”
mentioning
confidence: 99%
“…Additional file 1 : Table S3 shows the parameters available for each included study. Risk of bias assessment (Robins-I tool) revealed 4 studies with a low risk [ 31 , 34 36 ], 14 with moderate risk [ 6 , 8 , 19 , 30 , 33 , 37 44 ], and 30 with serious risk [ 4 , 18 , 21 29 , 32 , 45 60 ]. Three studies were categorized as critical risk [ 61 63 ] (Additional file 1 : Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…We identified three RCTs: two with mild to moderate ARDS patients [ 20 , 31 ]. And one with AECOPD patients on NIV [ 36 ]. The aim of the ARDS trials was to reduce the invasiveness of ventilation to an “ultraprotective level” in the ECCO 2 R arms, while standard “protective” ventilation was used in the control arms.…”
Section: Resultsmentioning
confidence: 99%
“…The eligible studies were conducted from 1994 to 2022 with a total number of 1173 patients. Among the included studies, two were conducted in multiple countries [ 18 , 23 ], two were from the United Kingdom [ 19 , 21 ], and other studies were conducted in France [ 22 ], America [ 20 ], Turkey [ 26 ], Germany [ 25 ], Italy [ 24 ]. The sample sizes ranged from 18 to 412, with a median of 50 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Within the three RCTs, no statistically significant difference was observed in overall mortality between the ECCO 2 R group and control group (RR 1.05, 95% CI 0.83 to 1.32, p = 0.70, I 2 =0.0%, Figure 2 ). The other RCT [ 21 ] and observational studies [ 22–26 ] targeted patients with ARF secondary to COPD. Pooled result of the five studies also showed similar overall mortality (RR 0.80, 95% CI 0.58 to 1.11, p = 0.19, I 2 =0.0%, Figure 3 ), and the result was largely dependent on observational studies (RR 0.77, 95% CI 0.55 to 1.08, p = 0.13, I 2 =0.0%, Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%